1995
DOI: 10.3346/jkms.1995.10.5.373
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between tissue plasminogen activator, plasminogen activator inhibitor and CT image in chronic subdural hematoma

Abstract: The present study was performed to investigate the relationship between the concentrations of tissue-type plasminogen activator (t-PA) and plasminogen activator inhibitor (PAI) and the CT images in 23 cases of chronic subdural hematomas (SDHs). The concentrations of t-PA and PAI-1 were quantified by enzyme-linked immunosorbent assay (ELISA). Chronic SDHs were divided into five groups according to their appearance on computed tomography: high-density (n = 4), isodensity (n = 8), low-density (n = 5), mixed-densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…15;16 The concentration of tissue plasminogen activator (t-PA) is highest and the concentration of plasminogen activator inhibitor (PAI) is lowest in mixed-density CSDHs. 17 This suggests that fibrinolytic activity is highest in mixed-density CSDHs. Highmolecular weight fibrin degradation products (FDPs) inhibit coagulation, platelet aggregation, fibrin polymerization, and promote the activity of t-PA. 17 The FDPs also have angiogenic activity and stimulate fibroblast proliferation, possibly contributing to CSDH membrane formation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…15;16 The concentration of tissue plasminogen activator (t-PA) is highest and the concentration of plasminogen activator inhibitor (PAI) is lowest in mixed-density CSDHs. 17 This suggests that fibrinolytic activity is highest in mixed-density CSDHs. Highmolecular weight fibrin degradation products (FDPs) inhibit coagulation, platelet aggregation, fibrin polymerization, and promote the activity of t-PA. 17 The FDPs also have angiogenic activity and stimulate fibroblast proliferation, possibly contributing to CSDH membrane formation.…”
Section: Discussionmentioning
confidence: 97%
“…17 This suggests that fibrinolytic activity is highest in mixed-density CSDHs. Highmolecular weight fibrin degradation products (FDPs) inhibit coagulation, platelet aggregation, fibrin polymerization, and promote the activity of t-PA. 17 The FDPs also have angiogenic activity and stimulate fibroblast proliferation, possibly contributing to CSDH membrane formation. 18 The FDP level is highest in the mixed-density group.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…59 60 The high concentration of vascular endothelium derived growth factor (VEGF), for example, could be involved in the formation of the haematoma membranes. Furthermore, the haematoma fluid contains inflammatory mediators [61][62][63] and fibrinolytic factors [64][65][66][67][68][69][70][71][72][73][74][75][76] which all may play a role in the further development of the haematoma. The risk of recurrence is increased when the concentration of fibrinolytic factors remains high in the postoperative drainage fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that local anticoagulation and inflammatory changes may influence the pathogenesis of CSDH, although the process has not been clearly elucidated. 16,28,32,35,38) The transformation of traumatic subdural hygromas into CSDH has been discussed in several studies. 7,23) Computed tomography (CT) of CSDH often shows changes in the components of hematomas, and there may be an association between CT appearance and altered cytokine levels in CSDH.…”
Section: Introductionmentioning
confidence: 99%